Introducing S-RILS and D-RILS as refractive index limited optical biosensors in multiple nanolayers - Nasrin Bouzari; Jafar Mostafavi Amjad; Ramin Mohammadkhani; Peyman Jahanshahi (Materials Research Express, 2020)
The amplitude and phase sensitivities of a sensor with a multiple nanolayers consisting of gold-silicon dioxide-gold (Au-SiO _2 -Au) are investigated. The proposed sensor has the ability to limit to the certain regions of the sensing medium refractive index n _s . The number of these regions can be increased by increasing the thickness of the silicon dioxide layer ( ${{\rm{d}}}_{SiO_{2}}$ ). The results show that for the ${{\rm{d}}}_{SiO_{2}}=200\,nm$ the sensitivity has a nearly Gaussian in shape which its position depends on the refractive index of the prism n _p . This type of sensor is introduced as a singlet refractive index limited sensor (S-RILS) that is useful tool in the detection of the target sample optical properties with certain refractive indices. It is found that two nearly Gaussian curves are generated in the amplitude and phase sensitivities for the ${{\rm{d}}}_{SiO_{2}}=450\,nm$ , which is introduced as a doublet refractive index limited sensor (D-RILS). The optical properties of the mixture samples can be detected by D-RILS, in while the S-RILS is used to detect the optical properties of single samples. The efficiency of the sensors can be improved by adding the titanium or titanium-graphene layers. The results exhibit that the optimal amplitude and phase sensitivities occur for multiple nanolayers (Ti-Au-SiO _2 -Ti-Au).